Lectures on the book of Daniel with expository notes on "The times of the Gentiles" and prophetic subjects - Ritchie, John, 1853-1930 (Kilmarnock, Scotland John Richie)
Includes index.
Brethren writer. Preface dated 1915.
Keywords: Bible. O.T. Daniel -- commentaries